2023
DOI: 10.2147/orr.s340531
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acromioclavicular Injuries – Current Concepts

Abstract: Introduction Treatment of a patient with acromioclavicular joint (ACJ) injury remains challenging for orthopedic surgeons. To date, there is debate over the optimal management of ACJ injuries. This review provides an overview of assessment, treatment, and future perspectives for the treatment of and research into ACJ. Material and Methods A scoping literature review was performed. The search was built including the following terms: acromioclavicular joint injuries or di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Since the best treatment of ACJ dislocation is still debated [ 6 ] today, we did not take an aggressive approach and decided not to perform a surgical treatment of this second injury. The excellent results at mid-term follow-up comfort us in this strategy and are consistent with other few cases of non-operative approach reported in the literature [ [7] , [8] , [9] , [10] ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the best treatment of ACJ dislocation is still debated [ 6 ] today, we did not take an aggressive approach and decided not to perform a surgical treatment of this second injury. The excellent results at mid-term follow-up comfort us in this strategy and are consistent with other few cases of non-operative approach reported in the literature [ [7] , [8] , [9] , [10] ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of the modern techniques include addressing the CC ligaments in isolation with constructs using suture suspensory construct, synthetic devices, hardware, and/or graft tissue. 5 , 13 , 15 , 16 , 17 , 21 , 24 , 27 , 30 Additionally, nonanatomic CC reconstruction options utilizing a hook plate and transfer of the CA ligament (Weaver-Dunn procedure) and modifications thereof have also been used. Over time, anatomic versus nonanatomic reconstruction options of the CC ligaments have been evaluated biomechanically.…”
Section: Acromioclavicular (Ac) Joint Anatomy and Biomechanicsmentioning
confidence: 99%
“…Two recent studies have shown good results with nonsurgical treatment of type V dislocations questioning the necessity of surgical treatment for this type [16,38]. Rockwood type III is the most common type of AC joint dislocation, but consensus regarding the treatment is lacking [10]. The majority of published studies compare predefined groups of patients treated surgically and nonsurgically and show comparable long-term clinical outcomes [5,14,32,38].…”
Section: Introductionmentioning
confidence: 99%